Efficiency of Production Structures in Agriculture - Kopeva, Diana; Madzharova, Svetla; Nikolova, Nina (Research Papers, 2012)
The study of farm efficiency before and after the EU accession gives an opportunity to be identified the trend of development of production structures in agriculture. Economic efficiency is an indicator, which precisely identifies to which extend farms use resources efficiently and allows analysis how and what combination of resources under relative prices leads to increase of efficiency.The aim of the paper is to analyzes and to study the efficiency of farms specialized in cereals, viticulture and horticulture, and to analyzes factors that have influence on their economic development and competitiveness.The economic efficiency analysis of firms consists of analysis of technical and allocative efficiency. The present research gives the opportunity economic efficiency of farms specialized in cereal, grape and vegetable production to be directly determined using stochastic frontier production analysis and the inefficiency model. The primary data base is compounded by structural questionnaires with the assistance of which are determined four conventional production factors and five socio-economical factors that influence over the agricultural production.